Ketuntasan Belajar Matematika Siswa Sekolah Dasar Melalui Pendekatan Realistik - Resa Nurlita; Puput Wahyu Hidayat; Iri Hamzah (CV. DIGITIAL EDUKASI NUSANTARA, 2026)
This research aims to improve the learning process and outcomes of Mathematics of flat building materials in grade V students of SDN 60/II Muara Bungo through the application of the Realistic Mathematics Education (RME) model. Preliminary observations show conventional teacher-centered learning with low levels of student engagement and learning outcomes; Only 18.18% of students achieved completeness. This class action research is carried out in two cycles, where each cycle consists of planning, implementation, observation, and reflection. The results showed a significant increase in educators' activities from the